MUSINGS IN THE GARDEN: SCULPTURE PARK AND THE AHMADU BELLO UNIVERSITY COMMUNITY - NADIR A. NASIDI; FAIDA SAMUEL (International Studies Journal)
The culture of sculpture parks is as old as art itself and exists in almost all communities across the globe. Such parks, their grandeur, serene outlook, artistic presence, and representations of a plethora of socio-political and economic issues mean a lot, especially to the people associating with them. Using an art historical analysis, primary and secondary data in the form of oral interviews, and extant literature, this paper studies the historical development of the Sculpture Garden of Ahmadu Bello University, Zaria focusing mainly on its features, and functions, particularly within the University community.  Although the Garden emerged from the necessity of providing space for the reservation and preservation of the outdoor sculptures produced by students ofthe Fine Art Department of the University, this paper argues that it now blossoms to provide a conducive atmosphere for the exhalation of emotion, empathy, love, and peaceful contemplation. This is absent in the few previous studies conducted on the Garden. This paper concludes that the Garden also serves many purposes different from art and aesthetics, including the proliferation of businesses while providing a serene environment for meetings, lectures, and shelter for lovers.